First record and new species of the genus Hebefustis Siebenaller & Hessler, 1977(Isopoda: Asellota: Nannoniscidae) from the deep Weddell Sea Basin - Kaiser, Stefanie (Zootaxa, 2008)
The ANDEEP (ANtarctic benthic DEEP-sea biodiversity, colonisation history and recent community patterns) cruises contributed immensely to the understanding of the deep Southern Ocean biodiversity, and study of the fauna, in particular the isopod crustaceans, which were revealed to be patchily rich. Most of the species found during the three ANDEEP expeditions were not only new to the region but also new to science. In the current paper a new nannoniscid species, Hebefustis clareolithis sp. nov., is described from the deep Weddell Sea Basin (Southern Ocean). Specimens of the new species were sampled during ANDEEP III in Antarctic summer 2004/05 and represent the first Southern Ocean record of the genus Hebefustis Siebenaller & Hessler, 1977. The new species closely resembles Hebefustis cornutus Siebenaller & Hessler, 1977 but can be distinguished from the latter by the number of flagellar articles of the female antenna, the shape of pleopod 1 and pleotelson in male. A key to the species in the genus Hebefustis is provided.